Viborče pravo v Ukraїnì u perìod sprob vìdrodžennâ ukraїns′koї deržavnostì pìslâ I svìtovoї vìjni - Pankevič, Ivan (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2011)
In the given article the issue of the election law in Ukraine during the attempts of Ukrainian statehood revival after World War II is examined. The electoral legislation of Ukrainian National Republic, during Pavlo Skoropadskyjs’ hetmanat, the Directory and the West Ukrainian National Republic are being analysed. In addition, the role of Ukrainian parliamentary representation in interwar Poland and its influence on politics of II Rzeczpospolita has been analysed.
Keywords: Ukraina po I wojnie światowej; prawo wyborcze; odradzanie ukraińskiej państwowości